The Federal Effort to Desegregate Southern Hospitals and the Black-White Infant Mortality Gap - D. Mark Anderson; Kerwin Kofi Charles; Daniel I. Rees (Institute of Labor Economics (IZA), 2020)
In 1966, Southern hospitals were barred from participating in Medicare unless they discontinued their long-standing practice of racial segregation. Using data from five Deep South states and exploiting county-level variation in Medicare certification dates, we find that gaining access to an ostensibly integrated hospital had no effect on the Black-White infant mortality gap, although it may have discouraged small numbers of Black mothers from giving birth at home attended by a midwife. These results are consistent with descriptions of the federal hospital desegregation campaign as producing only cosmetic changes and illustrate the limits of anti-discrimination policies imposed upon reluctant actors.
Keywords: I14; I18; N32; 330; hospital desegregation; black infant mortality; Medicare; civil rights